Suficiência amostral e preditores ambientais da vegetação de sub-bosque da Mata Atlântica de Santa Catarina, Brasil - Leila Meyer (2015)
The present work is arranged in two chapters. In the first chapter, we evaluated the different sampling strategies adopted by Inventário Florístico Floresta de Santa Catarina (IFFSC), in order to identify the most appropriate strategy to capture the species composition and richness, and the patterns of diversity distribution. To accomplish this goal, we used different methods to test sampling sufficiency. Three sampling strategy were investigated: Strategy 1) sample plot with 100 m2 and inclusion of individuals with height 150 cm and DBH (Diameter at Breast Height) < 10 cm covering all Santa Catarina state; Strategy 2) sample plot with 400 m2 and individuals with height 150 cm and DBH < 10 cm covering only the Evergreen Rainforest of Santa Catarina; Strategy 3) sample plot with 400 m2 and individuals with height 50 cm and DBH < 10 cm covering only the Evergreen Rainforest. With more intensive sampling strategy (Strategy 3) more sample plots reached sampling sufficiency and more species and rare species were sampled. More endangered and rare species were recorded by study sites with sampling strategy 3. However, less intensive sampling (Strategies 1 and 2) can be used to recover coarse patterns of diversity distribution. In the second chapter, we investigated the influence of human impacts,landscape structure, tree component structure, climate, soil, topography and space variables on the species composition, diversity and structure of the understory in Evergreen Rainforest of Santa Catarina state. An important proportion of species composition, diversity and structure variance was explained by variables related to human impacts (human impacts and landscape structure variables), compared to the proportionsexplained by other environmental and spatial variables. The size and shape of the forest fragments, selective logging and hunting within the sample plots, exotic species monocultures surrounding sample plots seem to be the main variables related to human impacts that affected understory vegetation. Species composition was also partly explained by mean temperature of warmest quarter, density of tree component, calcium and soil pH. Species diversity was partly explained by soil cation exchange capacity, and understory structure, by altitude and actual evapotranspiration.